2017
DOI: 10.1016/j.istruc.2017.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Design of Composite Cold-Formed Steel Flooring Systems

Abstract: Recently conducted experimental and numerical investigations have shown that mobilisation of composite action within systems comprising cold-formed steel beams and wood-based floorboards is feasible and can lead to substantial improvements in structural performance. However, no design rules have yet been established for these systems in order to allow the beneficial effect of composite action to be exploited. In this paper, proposals for the design of such systems are devised and their theoretical basis is pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 3 publications
(28 reference statements)
0
52
0
Order By: Relevance
“…Degradation of the moment resistance with high levels of shear can be observed in Fig. 5, where the applied moment M Ed normalised by the moment capacity M c,Rd is plotted against the applied vertical shear force V Ed normalised by the shear resistance V b,Rd for all the physical tests and numerical simulations reported in [3] and [4] respectively. It is evident that an appropriate allowance should be made, accounting for the effect of the design shear force V Ed on the moment resistance M c,Rd .…”
Section: Interaction Of Bending and Shearmentioning
confidence: 99%
See 2 more Smart Citations
“…Degradation of the moment resistance with high levels of shear can be observed in Fig. 5, where the applied moment M Ed normalised by the moment capacity M c,Rd is plotted against the applied vertical shear force V Ed normalised by the shear resistance V b,Rd for all the physical tests and numerical simulations reported in [3] and [4] respectively. It is evident that an appropriate allowance should be made, accounting for the effect of the design shear force V Ed on the moment resistance M c,Rd .…”
Section: Interaction Of Bending and Shearmentioning
confidence: 99%
“…spacing of cold-formed steel beams employed for the examined flooring systems is 600 mm. Since the conducted experiments and numerical simulations have shown that there is no shear lag for this spacing [3,4], the effective width of the floorboard b eff can be taken equal to the spacing of the beams (i.e. 600 mm).…”
Section: Attained Degree Of Shear Connectionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can also be observed that the experimental flexural stiffness for specimens C-150-A (EIexp = 2823 kN.m 2 ± 4.2%) almost coincides with the analytical flexural stiffness obtained assuming full composite action, indicating that the specimen is nearly fully composite and that a high shear transfer occurs using such connection detail. Table 3 presents predictions of the flexural stiffness of the tested floors derived using existing models in [1], [6] and [9] as well as their deviation from experimental data. For each connection type, the analytical flexural stiffness was determined using results from the average pushout tests (in particular, k0.75).…”
Section: Analytical Predictions 41 Full-composite Actionmentioning
confidence: 99%
“…Such improvements are influenced by the spacing of shear connectors [3,4], connection detail (e.g. screws or bolts [5] with or without the presence of structural adhesives [3]), span length [6], joist gauge [3], and the type and depth of floor boards [9].…”
Section: Introductionmentioning
confidence: 99%